1997
DOI: 10.3181/00379727-214-44098
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Metabolism and Thyroid-Related Functions in Organisms Lacking Thyroid Follicles: Are Thyroid Hormones also Vitamins?

Abstract: Thyroid-related functions in organisms devoid of follicular thyroid tissue have been reviewed. In the lamprey, a primitive vertebrate, the larva concentrates iodide and synthesizes thyroid hormones (TH) by iodoperoxidase (IP)-mediated iodination of a thyroglobulin (TG)-like molecule in a subpharyngeal afollicular endostyle. The endostyle is the thyroid homolog, and it reorganizes into a follicular thyroid at metamorphosis to the adult. Ascidians and amphloxus, invertebrate protochordate relatives of vertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 75 publications
(95 reference statements)
2
86
0
6
Order By: Relevance
“…One study reported that THs accelerated metamorphosis in the mollusk abalone (Fukazawa et al, 2001) and another one in a crustacean [a prawn (Roustaian and Gaik, 2006)]. In contrast, THs did not seem to have any effect on the crustacean Daphnia (Kashian and Dodson, 2004) in accordance with the observation that no endogenous TH is present in this species (Eales, 1997). Consequently, hypotheses on the roles of THs or other derivatives and TR in protostomes can only be tentative: a potential responsiveness to THs would imply a very ancient function of TR as the TH receptor or, on the other hand, the establishment of an alternative function would imply an evolutionary shift.…”
Section: Discussionmentioning
confidence: 62%
“…One study reported that THs accelerated metamorphosis in the mollusk abalone (Fukazawa et al, 2001) and another one in a crustacean [a prawn (Roustaian and Gaik, 2006)]. In contrast, THs did not seem to have any effect on the crustacean Daphnia (Kashian and Dodson, 2004) in accordance with the observation that no endogenous TH is present in this species (Eales, 1997). Consequently, hypotheses on the roles of THs or other derivatives and TR in protostomes can only be tentative: a potential responsiveness to THs would imply a very ancient function of TR as the TH receptor or, on the other hand, the establishment of an alternative function would imply an evolutionary shift.…”
Section: Discussionmentioning
confidence: 62%
“…of the complementary enzymatic dyad of halogenation/ dehalogenation (for review Eales (1997) and Valverde-R et al (2004)). Indeed, current information supports the notion that the vertebrate thyroid gland, as well as the endostyle and subpharyngeal gland in invertebrate chordates, may have evolved from a common ancestor (for review Kluge et al (2005) and Paris et al (2008)).…”
Section: Phylogeny Of Deiodinasesmentioning
confidence: 99%
“…In vertebrates, iodine is critical for the synthesis of iodothyronines or thyroid hormones (THs), which, according to the ontogenetic stage of the organism, regulate early and postembryonic developmental processes and metabolic balance (Eales 1997, Valverde-R et al 2004, Yun et al 2005, Tata 2006). The major TH in circulation is thyroxine (T 4 ) whose synthesis is restricted to the thyroid gland.…”
Section: Introductionmentioning
confidence: 99%
“…The outer regions of the U-shaped ascidian endostyle traditionally have been considered to share a common evolutionary origin with the vertebrate thyroid gland, based on the finding that both organs sequester iodine and display thyroid peroxidase activity (reviewed by Eales, 1997).…”
Section: Endostylementioning
confidence: 99%
“…The feeding basket of the adult contains gill slits that appear to share a common origin with the gill slits of other chordates (Aros and Viragh, 1969). Likewise, the endostyle of the adult ascidian is a homolog of the vertebrate thyroid gland, sequestering iodine and producing thyroid hormone (Eales, 1997).…”
Section: Introductionmentioning
confidence: 99%